Perspectives on the Role of Fospropofol in the Monitored Anesthesia Care Setting - Joseph V. Pergolizzi; Tong J. Gan; Stanford Plavin; Sumedha Labhsetwar; Robert Taylor (Anesthesiology Research and Practice)
Monitored anesthesia care (MAC) is a safe, effective, and appropriate form of anesthesia for many minor surgical procedures. The proliferation of outpatient procedures has heightened interest in MAC sedation agents. Among the most commonly used MAC sedation agents today are benzodiazepines, including midazolam, and propofol. Recently approved in the United States is fospropofol, a prodrug of propofol which hydrolyzes in the body by alkaline phosphatase to liberate propofol. Propofol liberated from fospropofol has unique pharmacological properties, but recently retracted pharmacokinetic (PK) and pharmacodynamic (PD) evaluations make it difficult to formulate clear conclusions with respect to fospropofol's PK/PD properties. In safety and efficacy clinical studies, fospropofol demonstrated dose-dependent sedation with good rates of success at doses of 6.5 mg/kg along with good levels of patient and physician acceptance. Fospropofol has been associated with less pain at injection site than propofol. The most commonly reported side effects with fospropofol are paresthesia and pruritus. Fospropofol is a promising new sedation agent that appears to be well suited for MAC sedation, but further studies are needed to better understand its PK/PD properties as well its appropriate clinical role in outpatient procedures.